Upper Quarter Injury Rates and Risk in United States High School Athletes Prior To and During the Prolonged Sport Stoppage - Garrett Bullock; Charles Thigpen; Albert Prats-Uribe; R. Gill Gilliand; Ellen Shanley (International Journal of Sports Physical Therapy)
# Background